O direito fundamental ao trabalho na Constituição Federal de 1988 - Cervo, Karina Socal (My University, 2014)
This dissertation has as object the basic right for work and its multiple dimensions. In the Federal Constitution of 1988, the work is one of the beddings of the Democratic State of Right (art. 1º, IV), a basic right the installments (article 6º), a bedding of the economic order (article 170, caput) and base of the social order (article 193). Not withstanding this position normativelly detached, the Constitution did not specify the content and range of the basic right for work. The specification requires an analytical and constructive work of the Constitution interpreters. In this inquiry, the analytical method is used, priorizing the dogmatic study of the basic right for work, with the materials from the sources of law, specialized literature and jurisprudence. Each one of the of basic right for work dimensions was studied where it can be unfold, that is, while right of protection, counsel, organization and to procedure and installment in strict sense. The minimum content of the basic right to the work is delimited, what prima facie can be demanded from State. Narrow existing connection is identified between the basic right for work and the principle of the human being dignity. It demonstrates that one is affected when the real value of another is not recognized and promoted. The promotion and effectiveness of the right for work imply the aid to compensation of social inequalities, in exercise of real and effective freedom and of equality and, consequently, in the enjoyment of life dignity. However, it is not enough to recognize work as the value of basic right, but is necessary to become it viable. In this context, the main today existing public politics in the area of right for work are analyzed. Systematic, efficient and including public politics are necessary condition for the satisfaction of basic right for work.
Esta dissertação tem por objeto o direito fundamental ao trabalho e suas múltiplas dimensões. Na Constituição Federal de 1988, o trabalho é um dos fundamentos do Estado Democrático de Direito (art. 1º, IV), um direito fundamental a prestações (art. 6º), um fundamento da ordem econômica (art. 170, caput) e base da ordem social (art. 193). Não obstante essa posição normativamente destacada, a Constituição não especificou o conteúdo e alcance do direito fundamental ao trabalho. A especificação requer um trabalho analítico e construtivo dos intérpretes da Constituição. Nesta investigação, utiliza-se o método analítico, priorizando-se o estudo dogmático do direito fundamental ao trabalho, com os materiais das fontes do direito, da literatura especializada e da jurisprudência. Estuda-se cada uma das dimensões em que se pode desdobrar o direito fundamental ao trabalho, ou seja, enquanto direito de defesa, de proteção, à organização e ao procedimento e a prestações em sentido estrito. Delimita-se o conteúdo mínimo do direito fundamental ao trabalho, aquilo que prima facie pode ser exigido do Estado. Identificase a estreita conexão existente entre o direito fundamental ao trabalho e o princípio da dignidade humana. Demonstra-se que esta é afetada quando não se reconhece e promove o real valor daquele. A promoção e efetivação do direito ao trabalho implicam o auxílio à compensação das desigualdades sociais, no exercício da liberdade e da igualdade reais e efetivas e, por conseqüência, na fruição da vida digna. No entanto, não basta reconhecer ao trabalho o valor de direito fundamental, é preciso torná-lo viável. Nesse contexto, analisam-se as principais políticas públicas hoje existentes na área do direito ao trabalho. Políticas públicas sistemáticas, eficazes e abrangentes são condição necessária para a satisfação do direito fundamental ao trabalho.
Keywords: Direito do trabalho; Trabalho; Direito fundamental; Efetividade; Política pública; Dignidade da pessoa humana; Constituição (1988); Work; Basic right; Effectiveness; Public politics; Dignity of the human being